2007
DOI: 10.1002/pssc.200674408
|View full text |Cite
|
Sign up to set email alerts
|

Role of hydrogen in the photoinduced evolution of porous silicon luminescence

Abstract: Photo-induced post preparation evolution effects in porous silicon were studied by IR, EPR, photoluminescence, and hydrogen effusion spectroscopies. The results show that two independent mechanisms are present during the photo-induced evolution. We also show that hydrogen photo-effusion takes place, in agreement with our previously proposed model. Photo-effusion experiments performed in vacuum, combined with IR and photoluminescence spectroscopies allow to discriminate the competing mechanisms present in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
8

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 12 publications
0
13
0
8
Order By: Relevance
“…Several authors studied the photo-oxidation effects of lightemitting PSi samples. 10,24,[27][28][29][30][31] Some results, however, contradict the fundamental PL properties. For example, some authors reported a redshift during photo-oxidation, 27 while others observed a blueshift.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…Several authors studied the photo-oxidation effects of lightemitting PSi samples. 10,24,[27][28][29][30][31] Some results, however, contradict the fundamental PL properties. For example, some authors reported a redshift during photo-oxidation, 27 while others observed a blueshift.…”
Section: Introductionmentioning
confidence: 97%
“…1,2 However, the as-prepared PSi surfaces have been shown to be unstable in room air especially under light illumination. [3][4][5][6][7][8][9][10] Several authors, therefore, investigated to stabilize PSi surfaces using various techniques, such as rapid thermal oxidation, 11 high-pressure water vapor oxidation, 12,13 carbon termination, 8,14 inorganic or organic film coating, 6,9,[15][16][17] anodic oxygen termination or oxidation, 7,18-20 and wet chemical treatment. 21 Hydrogen ͑H͒ is known to passivate Si surfaces by binding to Si dangling bonds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As we demonstrated previously [3], during the first stages of photo-oxidation, oxygen atoms displace hydrogen atoms preferentially from di-hydride sites. Although the breaking energy of Si-Si bonds is lower than that of Si-H (E(Si-H))ones, molecular H 2 formation is involved in the process, as usually occurs in effusion experiments [14,15]. The actual amount of energy needed to overcome the energy barrier E B should be: , labelled IP in Fig.…”
Section: Introductionmentioning
confidence: 98%